A Novel Saponin Stigmasta-7,16,25(26)-triene-3-O-β-D-glucopyranosyl-(1→5)-O-β-D-xylo-furanoside Isolated and Identified from the Stem of Pithecellobium dulce - Gupta, H.M.; Saxena, N.K. (Asian Journal of Chemistry, 2010)
A novel saponin stigmasta-7,16,25(26)-triene-3-O-β-D-glucopyranoside- (1→5)-O-β-D-xylo-furanoside has been isolated and identified from the stem of Pithecellobium dulce.